Juxtaposition of being professional and becoming professional: lessons from a nationwide study on teachers' conceptions of their professional status - Rizvi, Meher (Frontiers in Education, 2023)
Introduction When teachers are being professional in terms of professional standards, they follow their daily routine to produce quality work and wish to be seen as professionals in terms of their status. This is easier said than accomplished. In Pakistan, teaching has become a profession of last resort for many educated young individuals, despite efforts to raise the profession's status by investing in improving teacher management, fostering political support for teacher licensing, and prioritizing teacher development. Although there are examples where reform initiatives have shown positive outcomes in the classroom, the prevailing situation is such that these examples often go unnoticed due to the reforms failing to make a substantial impact, particularly in public school classrooms. Teachers are frequently criticized for their substandard practice and lack of rigorous preparation. The professional status of teachers, therefore, continues to show a declining trend. However, teachers seem to disagree with notions that appear to de-professionalize their profession. Methods Large-scale nationwide research was conducted to explore and understand teachers' perspectives on their professional status and the measures that have been taken to enhance their status from a broad perspective by using a survey design. Data were collected from 4,165 teachers from four provinces of Pakistan using a multistage stratified sampling technique to ensure the sample was representative of the entire country. The collected data were analyzed using both descriptive and inferential statistical techniques. Factor analysis was conducted to find the key underlying dimensions of attributes to unpack teachers' core professional competencies. Results The research study utilized the teachers' lens to highlight and discuss the interplay between how they see themselves as professionals in terms of their status and regard, how they strive to be professionals in terms of practicing professional standards (the being), and how various measures have been undertaken to enhance teachers' status so that they can be seen as a professional (the becoming). Discussion The key premise of the research study is that teachers, when they are being professional, they also need to be recognized as professionals for greater and demonstrable execution of professional standards at the classroom level.